A GIS‐Based Site Identification for the Seasonal Storage of Solar Heating: Promises and Pitfalls. Issue 2 (22nd November 2012) - Dolney, Timothy J.; Flarend, Richard
Abstract This research presents the use of GIS to identify potential locations of the Seasonal Storage of Solar Heating (S3H) within the state of Pennsylvania. The S3H utilizes a large pit to store thermal energy collected during the warm months for later use in the cold months. To maximize its overall efficiency, S3H must be built where several locational parameters occur in unison: abandoned mine lands (AMLs), institutions, soil type, and land use. These parameters were mapped using GIS with potential locations identified through the application of neighborhood statistics. Potential locations were verified through the use of aerial photographs, hillshades, and site visitations. The verification process revealed spatial inaccuracies associated with the AML dataset. As a result, the horizontal positional accuracy of AMLs was tested according to the Geospatial Positioning Accuracy Standards – National Standard for Spatial Data Accuracy (NSSDA). Results indicate larger than expected positional offset for a dataset that is crucial to funding the reclamation of AMLs.